PERCOBAAN APLIKASI LAPANGAN PENAMBAHAN LIMBAH POLIPROPILEN KE DALAM CAMPURAN BERASPAL DENGAN CARA KERING - Tjitjik W. Suroso (Direktorat Bina Teknik Jalan dan Jembatan, 2007)
To improve the quality of asphalt mix by adding polipropilen (waste material) in wet process has several constraints such as high temperature which generates smoke requires a mixer, three tones of asphalt residu left in the tank and it is an uneconomical use of resource. Therefore, another method of dry process should be experimented was experimented to add polipropilen into asphalt mixture namely by mixing polipropilen and hot aggregates at mix temperature obtained from laboratory tests. The field experiment results after six months show that the quality of asphalt mixture by dry process has a better performance than asphalt mixture using asphalt pen 60 such as greater stiffness modulus and dynamix stability, little rate of deformation, a greater degree of compaction, less rutting. Base on observation result using FWD comparing to road pavement with asphalt pen 60. The success of the experiment, mixing method by dry process has a good prospect to be applied in areas where mixer are not available. Key word: Asphalt , dry process, polipropilen, waste, density rut, mixed asphalt